OPOSISI BINER KESEJARAHAN INDONESIA PERIDOE REVOLUSI FISIK (1945-1949) DALAM FILM SOEGIJA (2012) & SANG KIAI (2013) - Sandy Allifiansyah (Universitas Bunda Mulia, 2017)
The binary opposition is a common way to drive the story. It is a basic way of thinking in popular movies. Through the method of narrative and semiotic analysis, this research reveals how binaries and the role of Hasyim Asy'ari as the leaders of Islam and Soegijapranata as Catholic leaders in the effort to defend Indonesia's independence during the physical revolution. The semiotics square concept of Greimas is used to understand and dissect the binary opposition structures contained in the historical narratives seen in Soegija (2012) and Sang Kiai (2013).Keywords: semiotics, movies, binary opposition, history